(3fXe GdeYdheGJ GdEOGQjI(B((3GdeaGgje GdCSGSjI(B)s - (3ShfjG eMeO(B, (3GdHcQjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2004)
(3eaghe fXe GdeYdheGJ,CfhGY fXe GdeYdheGJ GdeHjfI Ydi GdMGSH GdBdj,eONd GdfXe,JMdjd GdeaGgje GdCSGSjI ddeYdheGJ,ebOeI aj fXe GdMGSH GdBdj,OhQ fXe GdeYdheGJ GdESJQGJjLjI aj GdJfXje,fXe GdeYdheGJ GdEOGQjI hGdEOGQI,Gdgjcd GdJfXjej dfXe GdeYdheGJ GdEOGQjI,JWhjQ fXe GdeYdheGJ GdGOGQjI COhGJ eMdd GdfXGe,fXe GdeYdheGJ GdhXjajIs
(3HHdjhZQGajG(B:(3U(B.191:(3U(B.415-423s
Keywords: (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s